Ape house : a novel - Gruen, Sara. (New York : Spiegel & Grau, 2010)
When a family of bonobo apes who know American Sign Language are kidnapped from a language laboratory, their mysterious appearance on a reality TV show propels scientist Isabel Duncan, together with reporter John Thigpen, to rescue them.
Keywords: Human-animal relationships -- Fiction; Bonobo -- Fiction; Animal rights activists -- Fiction; Reality television programs -- Fiction